Metabolite profiles of formula milk compared to breast milk. (September 2016) - Scano, Paola; Murgia, Antonio; Demuru, Martina; Consonni, Roberto; Caboni, Pierluigi
Abstract: Breast milk (BM) feeding is the gold standard in neonate nutrition. When BM is not available it can be substituted or integrated with commercial formula milk (FM) usually sold under different brands and formulations. In this work, the low-molecular-weight hydrophilic compounds in milk were studied by gas chromatography electronic impact mass spectrometry (GC–MS), comparing eight different FM brands with BM samples. With the aid of multivariate statistical data analysis, a marked variability among FM brands, especially driven by the presence of prebiotics in their formulation, was highlighted. Quali-quantitative differences were found between FM and BM. Orotic acid and isomaltulose were found exclusively in FM, while phenylalanine and tyrosine levels were high in two FM brands. Moreover, higher levels of malic acid, sugars (glucose, fructose and galactose), and mannitol were detected in FM. On the other hand, BM showed a higher amino acid content. In conclusion, GC–MS proved to be a very sensitive analytical technique for the study of FM, highlighting metabolite differences among FM brands, and between FM and BM, that may have a possible strong impact on neonatal nutrition. Graphical abstract: Highlights: In formula milk the metabolites content greatly varied among brands. Formula milk samples containing oligosaccharides were rich in glucose and mannitol. Comparison of formula milk with breast milk showed high differences in metabolite profiles. Formula milk was richer in galactose, mannitol and malic acid and lower in aminoacids. Orotic acid and isomaltulose were exclusively found in formula milk.